LDL Cholesterol and the Development of Stroke Subtypes and Coronary Heart Disease in a General Japanese Population: The Hisayama Study - Imamura, Tsuyoshi; Doi, Yasufumi; Arima, Hisatomi; Yonemoto, Koji; Hata, Jun; Kubo, Michiaki; Tanizaki, Yumihiro; Ibayashi, Setsuro; Iida, Mitsuo; Kiyohara, Yutaka (Stroke (1970), 2009)
BACKGROUND AND PURPOSE—Although the relation between serum LDL cholesterol level and coronary heart disease (CHD) is well established, its relation with stroke subtypes is less clear. METHODS—A total of 2351 inhabitants age ≥40 years in a Japanese community were followed up for 19 years. RESULTS—During follow-up, 271 subjects developed stroke and 144 developed CHD. Whereas the age- and sex-adjusted incidences of CHD significantly increased with increasing LDL cholesterol levels (P for trend <0.001), the associations between LDL cholesterol level and the incidences of ischemic or hemorrhagic stroke were not significant. The age- and sex-adjusted incidences of atherothrombotic infarctions (ATIs) and lacunar infarctions (LIs) significantly increased with increasing LDL cholesterol level (P for trend=0.03 for ATIs and=0.02 for LIs), but no such association was observed for cardioembolic infarction. After multivariate adjustment, the positive associations of LDL cholesterol level with the risks of ATI and CHD remained significant (P for trend=0.02 for ATIs and=0.03 for CHD), whereas the association with LIs was not significant. The risk of ATI significantly increased in the fourth quartile of LDL cholesterol compared with the first quartile (multivariate-adjusted hazard ratio=2.84; 95% CI, 1.17 to 6.93). The multivariate-adjusted risks for developing nonembolic infarction (ATIs and LIs) and CHD were significantly elevated in the groups with elevated LDL cholesterol values with and without the metabolic syndrome. CONCLUSIONS—Our findings suggest that an elevated LDL cholesterol level is a significant risk factor for developing ATI as well as CHD, and these associations are independent of the metabolic syndrome.